METABOLITE ACTIVITY OF LACTIC ACID BACTERIA FROM SUMBAWA HORSE MILK, WEST NUSA TENGGARA, INDONESIA - Kusdianawati Kusdianawati; Apon Zaenal Mustopa; Fatimah Fatimah; Nurlaili Ekawati (JBIO: jurnal biosains (the journal of biosciences), 2023)
Sumbawa horse milk is one of the local products in Sumbawa (West Nusa Tenggara). There is no research so far which discusses the potencies of LAB metabolite compounds as antimicrobials and probiotics for treating Diabetes Mellitus type 2. This study aims to obtain the antimicrobial and inhibitory activity of the LAB-extracted metabolite compounds from Sumbawa horse milk collected from Penyaring village and Lennanguar village, Sumbawa, West Nusa Tenggara, Indonesia. LAB metabolites are extracted by using 96% ethanol. It has been found that metabolites extracted from media culture of LAB SKP K.9 (E. thailandicus) have the highest antimicrobial activity against S. aureus (ATCC 6538) (2.5 cm), S. typhimurium (2.5 cm), L. monocytogenes (BTCC B693) (2.53 cm) and EPEC K.1.1 (2.7 cm) when compared with other LAB isolates. Moreover, the inhibition of α-glucosidase enzyme obtained from LAB SKP K.5 isolate (L. garvieae) is 6.25%, 39.28% from LAB SKP K.9 (E. thailandicus), 53.57% from LAB SKP K.3 (W. confusa), 67.85% from LAB SKL K.4 (L. fermentum), and 78.57% from LAB SK 1.5 (E. faecium). The extract of LAB SK 1.5 metabolite compound (E. faecium) has the highest inhibitory activity against the α-glucosidase enzyme (78.57%) compared to other LAB isolates.